Wybrane aspekty kategorii kontaktu w dyskursie antynarkotykowym = The category of contact in anti-drugs discourse: Selected aspects - Kowal, Eliza (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper investigates the usage of the category of contact in anti-drugs discourse. Analyzing the example of an Australian brochure with the tools offered by Fairclough`s critical discourse analysis model, the author shows general tendencies and metaphors that run in the discourse. The main metaphor ?relation is an object? shows that relationships in a family as well as among friends function linguistically as an item that can be ?broken?, ?fixe? or ?repaired?.
Keywords: krytyczna analiza dyskursu; KAD; Fairclough; narkotyki; kampania społeczna; critical discourse analysis; CAD; drugs; public awareness campaigne